Estrategia de afiliación a la membresía de socios adherentes para el Club Universitario de Deportes - Aguado Iriarte, Diana Estefania (2024)
The present project consists of the elaboration and development of a campaign and communication strategy for the Club Universitario de Deportes (University Sports Club). A sports institution that was founded in 1924 by a group of students from various disciplines, including Arts, Medicine, Engineering, Agronomy and Education, from the Universidad Nacional Mayor de San Marcos, and whose main activity is soccer. Its legacy transcends national borders by being recognized as one of Peru's big three, and its prominence is further consolidated by being included in the select historical classification of the World Club Ranking, issued by the International Federation of Football History and Statistics, which underlines its outstanding position at a global level. The objective of this project is to create a strategic plan to increase the number of subscribers to the "Adherent Members" category, determining, segmenting and identifying the target audience in a precise manner and ending the year with 120 thousand of them, and, at the same time, to develop a communication strategy in which will achieve the loyalty of more fans of the U.